EFL Teacher’s Tactics In Teaching Speaking at Senior High School - Tarmin, Andi Masriadi; Aeni, Nur (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
This research is aimed to describe the strategies utilized by the Englsih teacher in teaching speaking to the tenth-grade students of SMA Islam Negeri Athirah Bone. This research explores how innovative methods improve students’ speaking proficiency, offering insights into adaptable strategies for language teaching. This study utilizes a qualitative research design focusing on interviews. The study was conducted with one English teacher as the research subject. The findings of the research indicate that the teacher utilized a variety of strategies, in this case, role-play, dialogue, group discussion, modeling use of media or technology, storytelling, peer teaching, simulation, interactive games, presentations, language games, think-pair-share, task-based learning, question and answer sessions, improvisation activities, use of authentic materials, and error correction and feedback sessions. It is concluded that the teacher utilized diverse strategies in teaching and speaking to the tenth-grade students of SMA Islam Athirah Bone. Additionally, the implication of this research is that educators in different levels of education can adopt a variety of interactive techniques to adapt to students’ various learning style and needs.